Use of 18F-fluorodeoxyglucose positron emission tomography-computed tomography in patients affected by polymyalgia rheumatica and persistent increase of acute phase reactants - Colaci, Michele; Dichiara, Jessika; Aprile, Maria Letizia; Ippolito, Massimo; Schinocca, Claudia; Guggino, Giuliana; Malatino, Lorenzo (Frontiers in Medicine, 2022)
Polymyalgia rheumatica (PMR) is an inflammatory disease affecting older adults characterized by aching pain and morning stiffness of the shoulder and pelvic girdles. Moreover, PMR can be associated with giant cell arteritis (GCA). Generally, PMR is highly responsive to steroids, reaching complete remission in the majority of cases. However, the possibility of occult diseases, including extra-cranial GCA, should be excluded. 18F-fluorodeoxyglucose positron emission tomography (18F-FDG-PET) is able to detect the presence of peri-/articular or vascular inflammation, which may be both present in PMR, thus representing a useful diagnostic tool, mainly in presence of extra-cranial GCA. We retrospectively evaluated all consecutive patients who received the diagnosis of PMR in our rheumatology clinic, classified according to the 2012 American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) criteria, in the period between April 2020 and May 2022. Among this case series, we selected the patients who underwent 18F-FDG-positron emission tomography (PET) because of the persistent increase of acute phase reactants (APR) besides the steroid therapy. Eighty patients were diagnosed with PMR. Nine out of them also presented arthritis of the wrists during the follow-up, whereas none showed signs of cranial GCA at the diagnosis. Seventeen out of eighty subjects (mean age 71.5 ± 7.5 years; M/F 2/15) presented persistent increase of erythrocyte sedimentation rate (mean ESR 44.2 ± 20.8 mm/h) and/or C-reactive protein (mean CRP 25.1 ± 17 mg/l), thus they underwent total body 18F-FDG-PET/CT. Large vessel 18F-FDG uptake indicating an occult GCA was found in 5/17 (29.4%) cases. Twelve out of seventeen (70.6%) patients showed persistence of peri-/articular inflammation, suggesting a scarce control of PMR or the presence of chronic arthritis. Finally, in 2 cases, other inflammatory disorders were found, namely an acute thyroiditis and a hip prosthesis occult infection. 18F-FDG-PET/CT in PMR patients with persistent increase of APR is a useful diagnostic technique in order to detect occult GCA, persistence of active PMR or other misdiagnosed inflammatory diseases.